Evidence of "Silent" Hepatitis B Virus Infection in Psoriasis, Vitiligo, and Pityriasis Rosea Cases: A Pilot Study - Ruchi Supekar; Subrata Roy; Abhishek De; Subhajit Biswas (Wolters Kluwer Medknow Publications, 2024)
Background Psoriasis (PS), vitiligo (VT), and Pityriasis rosea (PR) are chronic skin diseases often occurring as a consequence of exaggerated immune responses. These skin manifestations can be triggered as a result of the molecular mimicry between viral protein (s) and host protein (s), which could generate auto-antibodies. In addition, it can be hypothesised that skin diseases are manifestations of the reduced immunity that is observed in chronic hepatitis B virus (HBV)-infected individuals. Aims and Objective To investigate the presence of HBV in PS, VT, and PR cases and Human Herpes Virus (HHV) 6 and 7 in PR cases. Materials and Methods DNA extracted from healthy controls (n = 20), PS (n = 10), VT (n = 11), and PR (n = 12) were subjected to HBV-S gene-specific polymerase chain reactions (PCRs) and HHV 6-UL57 and HHV7-UL10 gene-specific PCRs. PCR products of positive samples (HBV and HHV 6 and 7 DNA) of expected length were bi-directionally sequenced using overlapping primers. Sequence identification was performed by NCBI BLAST and analysed by multiple sequence alignment. HBV DNA copy number was determined through quantitative real-time PCR. The blood samples were also tested for HBV serological markers and Interferon gamma (IFN-γ) by enzyme immunoassays. Results The PCR data and Immunoassay study revealed that seven out of 12 PR, six out of 10 PS, and six out of 11 VT cases had signs of HBV infection. HHV 6 DNA was detected in four, whereas HHV 7 DNA was found in two of the 12 PR blood samples. PR6 presented the evidence of both HHV 6 and 7 co-infections. Conclusion Observing the correlation of HBV with skin diseases, albeit at the pilot level, a larger study is warranted to identify HBV infection in skin disease patients. The evidence of HHV 6 and HHV 7 DNA in PR cases supports the HHV infection linkage with PR.